Identification of QTLs and new candidate genes affecting ear shank length via BSA-seq and transcriptomic analysis in maize - An, Hongzhou; Li, Kuiying; Liu, Xiaolan; Wu, Yuhua; He, Jianhan; Wang, Yanbing; Gao, Zengyu (Frontiers in Plant Science, 2026)
IntroductionThe ear shank, a short branch connecting the stalk and the ear, represented a key agronomic trait influenced both yield and plant architecture in maize, yet the molecular mechanism remained not fully understood.MethodsIn this study, BSA-seq was performed using an F2 population for two extreme bulks derived from the cross between WL134 and L135. Additionally, transcriptomic analysis and gene annotation were carried out to refine the association interval of ear shank length and identify crucial genes.Results and DiscussionA total of 14 QTLs for ear shank length were detected, which included 334 non-synonymous mutants, synonymous mutants and frameshift mutant genes. Among these loci, five were known to be associated with ear shank length, while nine were newly identified. 3,460 differentially expressed genes (DEGs) were screened through RNA-seq analysis of the ear shank at the silking stage in both parents. Thirteen new candidate genes were identified through the combined analysis of BSA-seq and RNA-seq, as well as gene function annotation and gene expression analysis. Based on functional predictions, the candidate genes Zm00001eb023400, Zm00001eb023420 and Zm00001eb050490, which encoded lytic transglycosylases, significantly associated with cell wall remodeling and degradation. The candidate genes Zm00001eb282410 and Zm00001eb282430 enriched the phenylpropanoid biosynthesis pathway and played important roles in the formation of the maize ear shank. These findings provided a foundation for understanding the molecular mechanisms regulating ear shank length in maize.